Editorial - Stefano Cozzolino; Anita De Franco (Transactions of the Association of European Schools of Planning)
This themed issue on “conformorality” is inspired by the work of Chiara Lisciandra, Marie Postma-Nilsenová, and Matteo Colombo (2013), which explores the tendency of individuals within a particular group or community to align with certain ideologies and values. The term “conformorality”, which combines the concepts of “conformity”, “conformism”, and “morality”, was first introduced into planning debates by Claudia Basta, the former coordinator of the AESOP Thematic Group on Ethics, Values, and Planning, in her thought-provoking presentation entitled “Unequal, thus Unjust?”. This presentation was delivered at a research seminar entitled “The Just City in Practice: Operationalising a Broad and Varied Concept,” which was held on August 21, 2020 in The Hague after the long period of social distancing that had been enforced due to COVID-19 restrictions. In Basta’s presentation, conformorality represented the widespread sentiment that exists between planning scholars that economic inequality equates to injustice; she discussed the limitations of this uncritical attitude.